1995
DOI: 10.1159/000126983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formalin-Induced Pain on ACTH, Beta-Endorphin, Corticosterone and Interleukin-6 Plasma Levels in Rats

Abstract: The behavioral and immunoendocrine effects of formalin-induced pain were studied in male rats following a subcutaneous injection of formalin (50 µl; 0.1%, F01 groups, 10%, F10 groups) or sham injection (control groups). After treatment, animals were tested in a transparent open field for either 30 or 60 min and thereafter sacrificed by decapitation. Plasma was collected for adrenocorticotropic hormone (ACTH), corticosterone, β-endorphin (β-EP) and interleukin-6 (IL-6) determinations. Pain-evoked responses (lic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 37 publications
(43 reference statements)
1
19
1
Order By: Relevance
“…63 For quantification of mechanical sensitivity thresholds, von Frey monofilaments (Stoelting, Wood Dale, IL) of graded bending forces (2.6-522 mN) were used as previously described. 6,63 Thermal and mechanical baseline measurements of both hind paws were taken for each animal before pain or stress stimuli and at 2,4,7,9,11,14,18, and 21 (where applicable) days following the treatments to measure hyper-or hypoalgesia. When the animals were killed, hind paws were removed just above the tibiotarsal joint and weighed to measure edema.…”
Section: Behavioral Measurementsmentioning
confidence: 99%
“…63 For quantification of mechanical sensitivity thresholds, von Frey monofilaments (Stoelting, Wood Dale, IL) of graded bending forces (2.6-522 mN) were used as previously described. 6,63 Thermal and mechanical baseline measurements of both hind paws were taken for each animal before pain or stress stimuli and at 2,4,7,9,11,14,18, and 21 (where applicable) days following the treatments to measure hyper-or hypoalgesia. When the animals were killed, hind paws were removed just above the tibiotarsal joint and weighed to measure edema.…”
Section: Behavioral Measurementsmentioning
confidence: 99%
“…Nociceptive stimulation elicits a plethora of neuroendocrine responses including arginine vasopressin (AVP) release (Kendler et al, 1978;Onaka et al, 1986Onaka et al, , 1996Onaka and Yagi, 1988) and activation of the hypothalamo-pituitary-adrenal (HPA) axis (Aloisi et al, 1995(Aloisi et al, , 1996Pacák et al, 1995;Culman et al, 1997;Persoons et al, 1997;Taylor et al, 1998). The formalin test for nociception is commonly used in rats and mice to assess the response of an animal to moderate, continuous pain (Abbott et al, 1982a), and this model is thought to resemble clinical pain (Dubuisson and Dennis, 1977;Dennis and Melzack, 1980;Abbott et al, 1982a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The formalin test is a stressful stimulus. However, it was reported that corticosterone did not increase after formalin injection in normal rats [15]. Another investigator reported that formalin stimulus activated the pituitary-adrenocortical system, but that the resulting release of corticosterone did not affect nociceptive processing [16].…”
Section: Discussionmentioning
confidence: 98%